A Comparative Study on the Molecular Characterization of E. Coli 0157 Isolated from Imported Beef in Malaysia and in Local and Imported Lamb in United Arab Emirates - A. Abudafeera, Sara Abdallay (2004)
This study was conducted to determine the incidence of E. coli 0157 in beef in Malaysia and lamb in United Arab Emirates. A total of 113 samples of beef (n = 25) and lamb (n = 88) were examined for the presence of E. coli 0157 which yielded 130 positive isolates for E. coli 01 57. All the isolates were found to be resistant to one or more of the fifteen antimicrobial agents tested. The strains isolated from lamb samples showed a high occurrence in multiple drug resistance. Plasmid analysis showed that most of the E. coli strains isolated from beef samples in Malaysia contained plasmids with size ranging from 1.3 to 60 MDa. The commonest plasmids of 60 MDa were observed in 3 1.8% of the strains. On the other hand, representative patterns for plasmid profiles among Esclzerichia coli O157 isolates from lamb possessed plasmid with molecular size ranging from 1.2 to 35.8 MDa. However, there did not appear to be a consistent relationship between a particular plasmid and resistance 10 an antibiotic. Two types of specific primer encoding the Shiga-like toxins gene, the SL7' I and SL7' 11 gene were utilized in the multiplex PCR assay. Analysis carried out demonstrated that Escherichia coli 0157 strains were positive for the presence sf Shiga-like toxins (stx) genes. Thus, analysis of all the /:: coli genome showed that mqst of isolates carried either both SIJT I and SI,T II genes or only the SI,T II gene. RAPD-PCR was used to generate polymorphic genomic fingerprints to discriminate the E. coli 0157 isolates. After a set of ten-mer oligonucleotides of 50% G-tC contents were screened, primers Gen1-50-9 (5 'AGAAGCGATG 3 ') and Genl -50,l 0 (S'CCATTTAC~ 3 ') were chosen whereby the primers generated reproducible and typeable results with bands ranging from 0.25 to 4.0 kilobase pairs. All the dendrogram were constructed utilizing the Gel Compar and RAPDistance software package based on the data retrieved from the presence or absence of banding pattern. Based on the dendrogram generated, there appears to be a genetic similarity at 70% among the strains issolated from beef and lamb. Two main groups were observed at 10% similarity level, group ane consists of E. coli 0157 isolates from imported beef in Malaysia and a few gf isolates of E. coli 0 157 from imported lamb in UAE. On the other hand, group two consists mainly of eight isolates of E. coli 01 57 from imported lamb in UAE. In the present study, all the molecular typing techniques have been used generally provided an additional value for assisting the molecular characterization of isolates of Escheric(ziu coli 0 157 utilized.